Green Collaboration for Sustainable Living: Learning, Empowerment, and Prosperity in Sukadamai village, Cikupa District, Tangerang - Sadi, Sumardi (Jurnal Pengabdian Masyarakat Bestari, 2024)
Green collaboration emphasizes cross-sector cooperation for environmental, economic, and social sustainability. This article explores the "learning, empowerment, and prosperity" principle in promoting sustainable living through various initiatives in Indonesia. The study, using a qualitative and case study approach, reveals that collaboration between government, communities, and the private sector effectively enhances awareness, skills, and local economies. It also addresses the challenges and solutions in implementing green collaboration. The 2024 UMT Real Work Lecture (KKN) in Sukadamai Village, involving 22 students under Dr. Ir. Sumardi Sadi's supervision, focused on improving local life quality through green collaboration.